An Analysis of Applications, Challenges and Security Attacks in MANET - Gnanaselvi, G. Sabeena; Ananthan, T.V (International Journal of Computer Sciences and Engineering, 2025)
Mobile ad-hoc networks (MANETs) are the independent collection of devices connected without the usage of manipulates base station or gets admission to factors. Mobile ad-hoc network includes a group of nodes outfitted with wireless interfaces, which are ready to communicate among themselves within the elimination of network infrastructure. In MANETs, nodes can operate records immediately with every different and every node perform like a router. As compared with stressed out networks. MANETs are greater defenseless because of safety attacks attributable to an infrastructure much less community. Presenting the protection measures has changed into a critical part in MANETs. This paper presents an impression of MANETs with various applications, plenty of attacks and demanding situations.